1986
DOI: 10.1177/00220345860650021701
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of the Effects of Plaque Thickness and Initial Salivary Sucrose Concentration on Diffusion of Sucrose into Dental Plaque and its Conversion to Acid During Salivary Clearance

Abstract: A mathematical model, written in FORTRAN, has been developed to simulate the interrelated processes of salivary sucrose clearance from the mouth, diffusion of sucrose into dental plaque, and conversion of sucrose to acid and glucan. Reaction of acid with enamel is not included in the model. A total of 28 parameters can be varied by the user, and the relative importance of the different factors affecting acid formation can be assessed. The output of the program gives sucrose and acid concentrations and pH at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 29 publications
4
46
0
1
Order By: Relevance
“…The effects of varying the bacterial film thickness gave results similar to those reported by Macpherson and Dawes [1991a], who demonstrated that increased film thickness caused a higher minimum pH following a sucrose rinse, in agreement with the trends predicted by the computer model of Dawes and Dibdin [1986]. This confirmed the in vitro model system as suitable for measuring pH changes at the base of a cariogenic film.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The effects of varying the bacterial film thickness gave results similar to those reported by Macpherson and Dawes [1991a], who demonstrated that increased film thickness caused a higher minimum pH following a sucrose rinse, in agreement with the trends predicted by the computer model of Dawes and Dibdin [1986]. This confirmed the in vitro model system as suitable for measuring pH changes at the base of a cariogenic film.…”
Section: Discussionsupporting
confidence: 86%
“…This confirmed the in vitro model system as suitable for measuring pH changes at the base of a cariogenic film. In a thick plaque, most of the glucose will be metabolised in the outer layers if the exposure is short, leaving less available to produce acid in the lower layers so that the minimum pH experienced at the plaque/tooth interface [Dawes and Dibdin, 1986] will be raised. Measurements of lactate concentrations and its spatial distribution support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is about half the thickness that we have calculated, but this may be due to the fact that, in their technique, the cheek was displaced from its normal position in close contact with the buccal surfaces of the teeth. In any event, the plaque is certainly not covered by a thick layer of saliva, as has been implicitly assumed in models of diffusion of substances in and out of plaque (Lagerl6f et al, 1984;Dawes and Dibdin, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ISFE T fissure plaque model is an interesting sys tem for studying the in situ diffusion o f various mole cules through plaque. The diffusion o f fermentable substrates, plaque acids and buffers through plaques o f defined thickness can be accurately monitored and it should be possible to test some o f the theoretical plaque diffusion models which have been presented by other investigators [Dawes and Dibdin, 1986], In addition, it is possible to use this system to study the effect of bacterial composition on plaque diffusion.…”
Section: Discussionmentioning
confidence: 99%